COMPARATIVE ASSESSMENT OF PAIN AND LIFE QUALITY IN THE PATIENTS AFTER OPEN AND VIDEO-ASSISTED LOBECTOMY FOR LUNG CANCER - R. I. Yurin; E. V. Levchenko; V. A. Gluscheko; A. E. Mikhnin; S. M. Ergnyan; L. V. Gorokhov; N. E. Levchenko; N. V. Khandogin (Вестник анестезиологии и реаниматологии)
The pain and pain syndrome remain to be serious problems of clinical medicine and surgery as one of its aspects. The positive correlation was found out between the type of surgery and post-operative pain in abdominal, thoracic and orthopedic surgeries. Materials and methods. Results of a questionnaire survey in 130 patients were analyzed; from 2015 to 2017 all those patients had lobectomies for lung cancer using video-assisted thoracoscopic or open accesses in the Thoracic Department of Petrov National Medical Research Center of Oncology. The intensity of pain and life quality in the post-operative period were assessed using visual analogue scales, the Wong-Baker FACES pain rating scale, verbal rating scales, and McGill pain questionnaire. In order to assess life quality, the non-specific questionnaire of SF-36 was used in the cancer patients and those enrolled in the clinical studies of EORTC QLQ-C30 including the special module of QLQ-LC13 for lung cancer patients. The obtained results were analyzed and it was found out that intensity of pain was statistically significantly lower in video-assisted thoracoscopic access versus thoracotomy (U = 678.00; p < 0.05). When using the questionnaires of SF-36 (U = 8,742.50; p < 0.05) and EORTC QLQ-C30 (U = 3,759.00; p < 0.05) and the special module of QLQ-LC13 for lung cancer (U = 4,243.00; p < 0.05), the obtained data also indicated the better life quality and functions, reduction of pathologic manifestations versus open surgical access. Conclusion: Reduction in the pain intensity and higher life quality were typical of surgeries with use of video-assisted thoracoscopic technologies versus classical open access.